Anti-Europeanism
XII, 200 p.
Keywords: The book analyzes different critical attitudes towards European integration from a multidisciplinary perspective. By applying both quantitative and normative-theoretical approaches, the contributors assess the causes and effects of the popularity of EU-critical positions and doctrines, such as souverainism, neo-nationalism and neo-populism. The book also presents country studies to compare populist movements and parties, such as the Five Stars Movement in Italy, Syriza in Greece and UKIP in the UK. It offers insights into the historical and normative roots of the diverse anti-European standpoints, and the various political demands and agendas connected with these views, ranging from rejections of EU institutions to demands for institutional reforms and propositions for alternative projects.